THE STATUS OF ADHERENCE IN LAMIVUDIN, TENOFOVIR AND DOLUTEGRAVIR USAGE TO TREAT HIV PATIENTS (Tạp chí Y học Cộng đồng, 2022)
Objective: To analyze the adherence to treatment with Lamivudin, Tenofovir,Dolutegravir in HIV patients at Long An General Hospital.Subjects and methods: Study of cross-sectional description, no interventionthrough retrospective medical records and interviews with questionnaires on 71 HIV/AIDS patients being treated with a 3-drug ARV regime of Lamivudin, Tenofovir,Dolutegravir including inpatient and outpatient treatment at the Department ofInfectious Diseases, Long An General Hospital.Results: The rate of adherence to ARV of study participants within 7 days beforethe time of interview was 63.4%. In which, 11.3% of patients missed at least onedose of the drug; 22.5% of patients took the medicine at the wrong time over 1 hourat least once; 5.6% of patients took ARV drugs incorrectly at least once. The studyresults showed that the relevant factors for ARV adherence were the patient’s age, theclinical stage before treatment and the home reminder method.Conclusion: The rate of adherence to treatment of ARV in study participants within7 days before the time of interview was 63.4%. Relevant factors for adherence totreatment of ARV were patient age, pre-treatment clinical stage, and home reminders.
Keywords: HIV, adherence to ARV treatment.